2007
DOI: 10.7748/ns2007.05.21.36.35.c4627
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of restraint and breakaway techniques in a psychiatric intensive care unit

Abstract: Restraint procedures, as taught in Control and Restraint training, appear to be an effective and reasonably safe means of manually controlling a violent client in psychiatric intensive care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The proportion of incidents resulting in restraint varied from 4% (Cheung et al. 1997), 12% (Torpy & Hall 1993), 23% (Parkes 2003, Southcott & Howard 2007), 26% (Tobin et al. 1991), 36% (Kennedy et al.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of incidents resulting in restraint varied from 4% (Cheung et al. 1997), 12% (Torpy & Hall 1993), 23% (Parkes 2003, Southcott & Howard 2007), 26% (Tobin et al. 1991), 36% (Kennedy et al.…”
Section: Incidencementioning
confidence: 99%
“…2008), more usually in the prone position (on the front) as apposed to the supine position (on the back). A much smaller study found that restraining a patient on a bed, face down on the floor or standing to be the most the most common restraint positions (Southcott & Howard 2007).…”
Section: Restraint Techniquesmentioning
confidence: 99%
“…Studies exploring the use of restraint have identified that the most common circumstances where restraint is utilized are in response to violent patient behaviour, abscondment, staff denial of a request, patient agitation, refusal of medication, self‐harm, verbal aggression and property damage (Gudjonsson et al . , Ryan & Bowers , Southcott & Howard , Bowers et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical intervention is the most commonly taught response for the management of violent behaviour in the UK and yet there is comparatively little research on its safety and effectiveness (Southcott and Howard 2007). In their study of inpatient aggression within a psychiatric inpatient setting, Shepherd and Lavender (1999) found that physical interventions were significantly more likely to be used than verbal interventions in managing aggressive incidents (approximately 65 per cent: 31 per cent respectively).…”
Section: Training In Physical Restraintmentioning
confidence: 99%